2017
DOI: 10.1037/xhp0000383
|View full text |Cite
|
Sign up to set email alerts
|

Articulatory information helps encode lexical contrasts in a second language.

Abstract: The present study examined whether obtaining additional articulatory information about the sounds of a difficult second-language contrast (English /ε/-/æ/ for German speakers) could help nonnative listeners to encode a lexical distinction between novel words containing these two categories. Novel words (e.g., tenzer-tandek) were trained with different types of input and their recognition was tested in a visual-world eye-tracking task. In Experiment 1, a baseline group was exposed to the words audio-only during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(65 citation statements)
references
References 59 publications
7
57
1
Order By: Relevance
“…A number of studies showed that additional information about differences between difficult L2 categories may help learners to start developing separate representations of these L2 sounds. This additional information can either be explicit instruction (such as corrective feedback, e.g., Saito & Lyster, 2012;Thomson, 2012; for an overview see Derwing & Munro, 2015, chapters 5 and 7) or when learning new words at a more advanced stage even implicit, for example, orthographic information or visible articulation (e.g., Escudero, Hayes-Harb, & Mitterer, 2008;Llompart & Reinisch, 2017). Future work will have to show how a combination of native-accented input, (meta) knowledge about L2 categories, and awareness of a foreign accent influence how learners' abilities develop in a second language.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies showed that additional information about differences between difficult L2 categories may help learners to start developing separate representations of these L2 sounds. This additional information can either be explicit instruction (such as corrective feedback, e.g., Saito & Lyster, 2012;Thomson, 2012; for an overview see Derwing & Munro, 2015, chapters 5 and 7) or when learning new words at a more advanced stage even implicit, for example, orthographic information or visible articulation (e.g., Escudero, Hayes-Harb, & Mitterer, 2008;Llompart & Reinisch, 2017). Future work will have to show how a combination of native-accented input, (meta) knowledge about L2 categories, and awareness of a foreign accent influence how learners' abilities develop in a second language.…”
Section: Discussionmentioning
confidence: 99%
“…The mean of the five responses was calculated so that each participant received one value that represented his or her "proficiency." MATERIALS Thirty-one English minimal word pairs were selected that differed in sound contrasts that have been shown to cause problems for German learners in production and perception (Llompart & Reinisch, 2017;Smith et al, 2009). Eleven minimal pairs were chosen to differ in the vowel contrast /e/-/ae/, seven pairs in the word-final voicing contrast in fricatives, and 13 pairs in the word-final voicing contrast in stops.…”
Section: Participantsmentioning
confidence: 99%
“…A well-replicated finding is that audio-visual speech training improves the ability to discriminate between non-native speech sounds (Hardison, 2003(Hardison, , 2005Hazan et al, 2005;Hirata and Kelly, 2010;Llompart and Reinisch, 2017). For example, Hazan et al (2005) found that Japanese speakers' ability to discriminate the English phonemes /b/ and /p/ from /v/, was improved by presenting each sound with its visual articulation.…”
Section: Introductionmentioning
confidence: 89%
“…Because accurate phonemic discrimination is crucial to language comprehension, much work has sought to find ways to enhance the learning of non-native speech sound contrasts. For instance, a number of behavioral studies have shown that the ability to discriminate between non-native speech sounds improves after seeing how the sounds are articulated (Hardison, 2003(Hardison, , 2005Hazan et al, 2005;Hirata and Kelly, 2010;Llompart and Reinisch, 2017). However, the effect this type of training has on the neural processing of non-native speech sound contrasts has received less empirical attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation